Protein aggregation profile of the human kinome - Graña-Montes, Ricardo; Sant'anna de Oliveira, Ricardo; Ventura, Salvador (Frontiers in Physiology, 2012)
Protein aggregation into amyloid fibrils is associated with the onset of an increasing number of human disorders, including Alzheimer’s disease, diabetes and some types of cancer. The ability to form toxic amyloids appears to be a property of most polypeptides. Accordingly, it has been proposed that reducing aggregation and its effect in cell fitness is a driving force in the evolution of proteins sequences. This control of protein solubility should be especially important for regulatory hubs in biological networks, like protein kinases. These enzymes are implicated in practically all processes in normal and abnormal cell physiology and phosphorylation is one of the most frequent protein modification used to control protein activity. Here, we use the AGGRESCAN algorithm to study the aggregation propensity of kinase sequences. We compared them with the rest of globular proteins to decipher whether they display differential aggregation properties. In addition, we compared the human kinase complement with the kinomes of other organisms to see if we can identify any evolutionary trend in the aggregational properties of this protein superfamily. Our analysis indicates that kinase domains display significant aggregation propensity, a property that decreases with increasing organism complexity.